Comparative characteristics of the meadow soils of the Crimean mountain plateaus - Kostenko, Igor; Nikiforov, Alexander; Abakumov, Evgeny (Hungarian Geographical Bulletin, 2023)
The results of studies of mountain-meadow soils of the Crimean Mountain plateaus (yailas) within the range of heights from 580 to 1,493 m a.s.l. are presented. The aim of the research is a comparative analysis of the full-profile soils of the mountain meadows distributed on the western and eastern parts of the Main Ridge of the Crimean Mountains and their correspondence to similar soils of nearby mountain ranges. According to the results obtained, the soils of the western yailas are classified as Phaeozems and Umbrisols, while the eastern ones are mostly classified as Chernic Phaeozems. Chernic Phaeozems differ from Phaeozems and Umbrisols by higher values of the humification rate and the optical density of humic acids. In the humus horizons of Phaeozems and Umbrisols, the average values of the of humification rate varied from 21 to 31 percent, and Chernic Phaeozems from 27 to 34 percent. The optical density varied from 12.7 to 18.7 in Phaeozems and Umbrisols, and from 22.2 to 24.2 in Chernic Phaeozems. The climatic feature of the western yailas is the predominance of winter precipitation, or their relatively uniform distribution between warm and cold seasons, while at the eastern yailas the precipitation of the warm season prevails which may be responsible for the revealed differences in soil properties.